HEMORRHAGIC STROKE PROFILE ON SALATIGA REGIONAL PUBLIC HOSPITAL PATIENTS - Garudadwiputra, Ian A; Silalahi, Lothar M M V; Manus, Widya C (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
ABSTRACTIntroduction: There is an increasing number of new hemorrhagic stroke cases from 2017 to 2018 on The Province of Central Java and Salatiga. A study of demographics, laboratory examination, radiology, outcome, risk factor, and clinical presentation on hemorrhagic stroke patients are rarely done at Salatiga Regional Public Hospital. Objectives: This study aims to describe the hemorrhagic stroke profile on Salatiga Regional Public Hospital patients. Materials and Methods: Hemorrhagic stroke inpatient of Salatiga Regional Public Hospital in the period between October 2018 and October 2019 is studied. Demographic, laboratory examination, radiology, outcome, risk factor, and clinical presentation data are reported. Results: From a total of 192 data gathered, 120 meet the inclusion and exclusion criteria. 47,5% male and 52,5% female with highest age range (55-64) 33%. The majority of patients came from outside of Salatiga city 71,7%. Patients with blood pressure classification stage 1 11,7%; stage 2 80%. Laboratory examination data shows 52,5% high leucocyte count; normal thrombocyte count; normal lymphocyte count; normal monocyte count; 72,5% high neutrophil count; 71,7% high Neutrophil-Lymphocyte Ratio; 89,2% high ureum level; normal creatine serum; 80% not at risk based on eGFR. Types of hemorrhages are ICH, IVH, and SAH with percentages 68,7%; 25,3%; 6% respectively. Basal Ganglia (48,1%) are the most common location for ICH and lateral ventricle (61,9%) are the highest for IVH. Clinical presentation for GCS (14-15) are the highest 58%. Patients with mortality are dominant in males with mean age 59,61 (year); followed by high counts of leucocyte, neutrophil, NLR, and ureum. Conclusion: Hemorrhagic stroke patients at Salatiga Regional Public Hospital are mainly female with the age range of 55-64 are the highest, came from outside of Salatiga city. The most frequent risk factor is hypertension. Most patients have GCS of 14-15 and stage 2 blood pressure classification. Most of the patient have leucocytosis, neutrophillia, high NLR and ureum level. ICH is the highest stroke subtype with the most frequent location of basal ganglia. More patients with good outcomes compared with a bad outcome.